PENGARUH IAA DAN BAP TERHADAP PERTUMBUHAN TANAMAN NILAM (Pogestemon cablin Benth) IN VITRO - Muhammad Hatta (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2008)
Effect of IAA and BAP on Growth of Patchouli (Pogestemon cablin Benth) In Vitro Muhammad Hatta, Mardhiah Hayati dan Ulfa Irayani Fakultas Pertanian Unsyiah Darussalam Banda Aceh ABSTRACT The research was aimed at understanding response of patchouli growth in vitro to concentration of IAA and BAP, and looking at interaction between both treatments. The experiment was arranged in a factorial randomized complete block design (RCBD) 2 x 6 with 5 replicates. Factors investigated were concentration of IAA (0 dan 1 mgl-1) and concentration of BAP (0.0, 0.4, 0.8, 1.6, 3.2 dan 6.4 mgl-1). Variables observed were shoot numbers, shoot height, and leaf numbers at 8 weeks after culturing. The results showed that there was interaction between IAA and BAP on leaf numbers of plantlet at 8 weeks after culturing, where the presence of IAA in the medium caused BAP to exert negative effect on lef formation. On shoot numbers and shoot height, the concentration of IAA and BAP did not exert any effect.